Molecular characterization and expression analysis of a suite of cytochrome P450 enzymes implicated in insect hydrocarbon degradation in the entomopathogenic fungus Beauveria bassiana - Pedrini, Nicolás (2010)
The insect epicuticle or waxy layer comprises a heterogeneous mixture of lipids that include abundant levels of long-chain alkanes, alkenes, wax esters and fatty acids. This structure represents the first barrier against microbial attack and for broad-host-range insect pathogens, such as Beauveria bassiana, it is the initial interface mediating the host-pathogen interaction, since these organisms do not require any specialized mode of entry and infect target hosts via the cuticle. B. bassiana is able to grow on straight chain alkanes up to n-C33 as a sole source of carbon and energy. The cDNA and genomic sequences, including putative regulatory elements, for eight cytochrome P450 enzymes, postulated to be involved in alkane and insect epicuticle degradation, were isolated and characterized. Expression studies using a range of alkanes as well as an insect-derived epicuticular extract from the blood-sucking bug Triatomas infestans revealed a differential expression pattern for the P450 genes examined, and suggest that B. bassiana contains a series of hydrocarbon-assimilating enzymes with overlapping specificity in order to target the surface lipids of insect hosts. Phylogenetic analysis of the translated ORFs of the sequences revealed that the enzyme which displayed the highest levels of induction on both alkanes and the insect epicuticular extract represents the founding member of a new cytochrome P450 family, with three of the other sequences assigned as the first members of new P450 subfamilies. The remaining four proteins clustered with known P450 families whose members include alkane monooxygenases.